Physics 10 - Khan ullah aamir (Islamabad National book foundation, 2025)
The Physics Grade 10 book covers key concepts of mechanics, waves, thermodynamics, electricity, magnetism, and modern physics. It explains natural laws and phenomena like motion, force, energy, sound, light, and electric circuits in a clear and structured way. The book connects theory with practical applications through experiments, numerical problems, and real-world examples, helping students develop analytical and problem-solving skills in physics.